EDUKASI HIPERTENSI MELALUI LEAFLET “TAAT DAN CERMAT” TERHADAP PERUBAHAN PENGETAHUAN LANSIA DALAM PENGELOLAAN HIPERTENSI - Wisnu Cahyo Prabowo; Zufiha Citra Utami Masdar; Yusuf Isro’ Ridhotulloh; Nur Viva Favorit (Universitas Mataram, 2026)
Hypertension is a non-communicable disease (NCD) that often occurs in the elderly. This disease can lead to serious complications if not properly managed. Increasing public knowledge, especially among the elderly, is a strategic step in promotive and preventive efforts to control hypertension. This community service activity aims to increase the elderly's knowledge regarding hypertension management through education using leaflets based on the behavior of